2017
DOI: 10.51200/ejk.v0i0.851
|View full text |Cite
|
Sign up to set email alerts
|

Economic Transition in Late Nineteenth Century Malaya: Malay Economy in Multiethnic Perspective

Abstract: This article discusses the economic aspect of the Malays in multiethnic perspective in Malaya in the late 19th century. It focuses on the central issue associated with the slow pace of Malay economic development and their reaction to the changing economic orientation from subsistence to capitalism. The main concern here is the assumption based on the general consensus that the involvement of the Malays in commercial activities in the late 19th and early 20th centuries was less eminent compared to other communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…It is for this reason that they are excluded from acquiring the Malay Reserved Land in Johor (Abdullah, 2009: 50. See also Abdullah, 2017Abdullah, & 2018. It is also found that a similar provision has also been applied in Kelantan and Terengganu (Wong, 1975: 512-3).…”
Section: Historical Legacy In Ethno-religious Affiliation In Malaysiamentioning
confidence: 93%
“…It is for this reason that they are excluded from acquiring the Malay Reserved Land in Johor (Abdullah, 2009: 50. See also Abdullah, 2017Abdullah, & 2018. It is also found that a similar provision has also been applied in Kelantan and Terengganu (Wong, 1975: 512-3).…”
Section: Historical Legacy In Ethno-religious Affiliation In Malaysiamentioning
confidence: 93%
“…Secara realistiknya, untuk membolehkan rakyat mula berkecimpung dalam aktiviti merkantilisme, mereka memerlukan pembiayaan daripada pihak pemerintah. Oleh itu, dapat diperhatikan bahawa orientasi kewangan ini telah menular ke dalam komuniti tani melalui peruntukan pinjaman pertanian yang bermula pada akhir abad ke-19 dan awal abad ke-20 (Abdullah, 2016). Namun begitu, boleh dikatakan bahawa sumber pinjaman ini terlalu kecil bagi menampung keseluruhan keperluan kos operasi mereka.…”
Section: Penularan Ekonomi Wang Dalam Kalangan Masyarakat Melayuunclassified